An Approach Method to Evaluate Wood Emissivity - Rui Pitarma; João Crisóstomo (Journal of Engineering)
Throughout the ages, wood has been used in constructions. Therefore, most of the built heritage is made with wooden structures. Wood is a renewable, versatile, long-lasting, and environmentally sustainable material. It is comfortable, is aesthetically very valued, and has crucial environmental importance. Thus, being a widely used long-life material, it requires techniques for monitoring its state of integrity. Inspection needs to be done in production, in the work site, and during its useful life. Infrared thermography (IRT) is a nondestructive, noninvasive, noncontact diagnostic technique. It evaluates the surface temperature of objects based on the emitted radiation. Nevertheless, the accurate measurement of temperature is strongly dependent on the emissivity value of the material. This paper presents an expedite method to measure wood emissivity values, using active infrared thermography. Wood samples of the Pinus pinaster species were used in the experiments. The thermal contrast of the samples was performed by applying three different heating methods: conduction, convection, and radiation. The emissivity values of the three tests were compared with each other and with data from the literature, showing satisfactory results and validating the presented methodology. The procedure can also be adopted, with some adjustments, to other materials and in situ analysis, contributing to emissivity measurements.